Birth Order and Sibling Sex Ratio in Androphilic Males and Gynephilic Females Diagnosed with Gender Dysphoria from Iran. Issue 6 (5th March 2020) - Khorashad, Behzad S.; Zucker, Kenneth J.; Talaei, Ali; Rajabzadeh, Farzaneh; Hamed, Zahra; Akbarian, Pardis; Blanchard, Ray
Abstract: Background: This study investigated the effect of older brothers on sexual orientation in male adults diagnosed with gender dysphoria and the effect of older sisters on sexual orientation in female adults diagnosed with gender dysphoria from Iran. Aim: To assess for the presence of a fraternal birth order effect in transgender androphilic males and a sororal birth order effect in transgender gynephilic females. Methods: The subjects were 92 transgender males and 107 transgender females (all of whom met the DSM-5 criteria for gender dysphoria), together with 72 male and 78 female clinical controls. All the transgender males were androphilic, all the transgender females were gynephilic (preferentially attracted to members of their own biological sex), and all of the clinical controls were heterosexual (none were transgender or had a diagnosis of gender dysphoria). Outcomes: In relation to the probands, we analyzed the sibship composition of our groups with regard to birth order and sibling sex ratio (brothers to sisters). Results: The results for the transgender males confirmed the findings of 2 recent meta-analyses that older brothers increase the odds of androphilia in later-born males. The results for the transgender females did not clearly confirm one previous finding that older sisters increase the odds of gynephilia in later-born females—a finding obtained in a relatively large study that included gynephilic cisgender girls as well as girls diagnosed with gender dysphoria who will probably be predominantly gynephilic. Clinical Implications: The fraternal (later-born) birth order effect that we found for the transgender androphilic males, similar to that found in gay men, suggests a common underlying causal mechanism. Strengths and Limitations: Our study on Iranian patients diagnosed with gender dysphoria provides further generalizability for the study of birth order and sibling sex ratio that has, more often than not, been restricted to Western samples of adults diagnosed with gender dysphoria. It would be important to study these variables in Iranian gay men and lesbian women (without gender dysphoria) to further examine evidence for cross-cultural similarities when compared to Western samples. Conclusions: In contrast to the well-established fraternal birth order effect for males, the possible sororal birth order effect for females needs to be examined with additional samples.